THE POTENTIAL OF MOLDOVA’S PRODUCTS ON GLOBAL AGRIFOOD MARKETS - Liliana CIMPOIES; Cornel COSER (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Competitiveness is regarded as the main source of export development on international markets. For Moldova, agrifood products are main exports commodities and represent about 45% in total amount of exported merchandises. In this paper we analyze the Moldova’s agri-food sector. The goal is to analyze the potential of Moldavian commodities on global agri-food markets and to assess the level of trade specialization. For research analysis data from the National Bureau of Statistics was used. The data analyzes the four sections of products and the 24 groups of commodities HS 2012 (belonging to agri-food products). The period researched is referred to the years 2001-2016. The assessment of trade advantages is carried out through the index of international specialization (RTA index). The results will allow to reveal the commodities with highest advantages for exports, to consolidate and improve Moldova’s situation on global agri-food markets.